Implementation Of Enterprise Resources Planning (Erp) Using Accurate Online Application In Managing Financial Information At Pt Dartim Agung Baihaqi - Nindi Suhendri (ConCEPt - Conference on Community Engagement Project, 2024)
This research aims to interpret the implementation of the ERP system, namely Accurate Online software, at PT Dartim Agung Baihaqi to increase the company's operational efficiency as well as record reporting that is good and easy to use. Data collection methods are carried out through interviews, observation and documentation. The results of this research are that the application of Accurate software makes it easier to input transactions, reduces errors in recording, and has a level of security regarding the risk of loss. Apart from that, supporting data such as financial reports will also be easier to access and more accurate because it will reduce the risk of human error and increase the efficiency of information delivery between departments and between parties